Epidemiological characteristics and trends of leprosy in children and adolescents under 15 years old in a low-endemic State in southern Brazil - Moraes, Paulo Cezar de (2021)
Leprosy is an infectious and contagious disease affecting skin and nerves. The number of cases in individuals under 15 years old is one of the parameters used in Brazil as an indicator of endemic permanence of the disease and its continuous transmission. Rio Grande do Sul State, in Southern Brazil, is low-endemic to leprosy. However, the disease remains a public health problem. This is a retrospective, observational and analytical study of a historical series of new cases of leprosy in children under 15 years old diagnosed in the period from 2000 to 2019, in all health units in Rio Grande do Sul State. Seventy-seven new cases were notified. The male gender was predominant in 53.2% of the cases (n=41). The average age was 10.4 years (standard deviation of 2.9), with predominance of the age group between 10 and 15 incomplete years old. The most frequent operational classification was multibacillary, in 62.3% of cases (n=48), and the most common clinical form was borderline, in 38.9% of cases (n=28). The predominant disability degree in the sample was grade zero, in 80.0% of the cases (n=60), but in 4.0% (n=3) the grade assessed was 2. In 54.0% of cases (n=27), bacilloscopy was performed, with positive results in 36.0% (n=9) of the exams. Multibacillary cases, with physical disability and/or positive bacilloscopy, draws attention that that the diagnosis is frequently not made in early stages.